ATTITUDE TOWARDS MASS OPEN ONLINE COURSES AS A FORM OF NON-FORMAL EDUCATION - Dehtiarova, Nelia; Hontar, Olena; Vernydub, Halyna (Physical and Mathematical Education, 2022)
Formulation of the problem. Non-formal education is becoming more and more popular. Non-formal education includes professional courses with a specific target audience, professional internships, mass open online courses, public education. Online courses that are in demand and their number is constantly increasing. Such courses are designed to expand the understanding of a particular subject of study or help to understand a completely new direction. Оpen courses are offered both on a free and paid basis. At present, it is believed that they are becoming popular due to the fact that higher education institutions must demonstrate the introduction of elements of non-formal education in the educational process. The purpose of this study was to find out the attitude of students to the massive open online courses and the reasons for choosing this type of education, which will allow you to build criteria for building a quality online course. Materials and methods: systematic analysis of scientific and methodological literature, comparison and synthesis of theoretical investigations of domestic scientists, questionnaires, generalization of personal experience. Results. Platforms on which paid and free online courses are available were analyzed: VUM, Dija. Digital Education, EdEra, Geek Brains, Laba, Prometheus, Wisecow. The paper provides links to these platforms and topics of the courses presented. Given the popularity of these courses among Ukrainian users, a survey was conducted on the reasons for choosing a particular platform and those that encouraged non-formal education instead of studying in school classrooms or university classrooms. Conclusions. The results gave grounds to claim that the main reasons why users start searching and taking online courses are their own desire for self-development and the requirement of the educational institution. This may indicate both informing about the existence of such a possibility, as well as a formal approach to such education, which will be studied in further research by the authors. Most often, respondents chose Prometheus, Action platforms. Digital Education and EdEra. At the same time, 65% chose free courses, and 35% took paid courses, which also indicates that such courses are currently available. Massive open online courses are an alternative to improving your skills, as well as to understand whether a particular direction is suitable for a particular person.